AgroclimR: an Agro-Climate Seasonal Forecast tool for Central America - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
The tool was developed in 2020 and was made available to the Central America ministries of agriculture staff through training in the Agricultural Application Forum linked to the CA-COF. Continuous improvements in the tool will be made until the end of 2021 to ensure the tool reaches scale